Al-Tafkīr al-Islāmī ‘an Taḥrīr al-Mar’ah bi Indūnīsiyā - Emzi Netri (Center for Study of Islam and Society (PPIM) Syarif Hidayatullah State Islamic University, 1997)
The generally weak position of women in Muslim society has given birth to a movement and thought among Indonesian Muslims concerning women's emancipation. Prominent figures have critized Muslim undersanding of women's position inherited from generation to generation for inferior and subordirate position of women in socicty. According to these figures, Islam is God's mercy for all and, as such, Islam cannot possibly treat men as special while regarding women as having a lower status. Although critical of how Islam understood women status, their conceptualization and articulation of the problem has differed according to the historical period and context in question.DOI: 10.15408/sdi.v4i4.769